Price Transmission and Market Concentration: An Investigation into the South African Dairy Industry - Ramakgasha, Molobe Joyce; Thaba, Tshephi Kingsley (International Journal of Economics and Financial Issues, 2026)
This research examines asymmetric price transmission and its link to market concentration in South Africa's dairy value chain, employing econometric techniques including Error Correction Models (ECM), Granger causality tests, and cointegration analysis. Using monthly price data (2000–2024) from farm-gate, processor, and retail levels. Employing ADF/PP unit root tests, Johansen cointegration, ECM, Granger causality, and HHI. The study identifies asymmetric price transmission characterized by stronger pass-through from retail to processor prices than from processor to farm-gate prices. Unit root tests confirm stationarity after first differencing (I(1)), while Johansen cointegration reveals long-run equilibrium between farm and retail pairs. ECM results demonstrate a 32% speed of adjustment to disequilibrium, with farmgate exerting disproportionate influence (51% long-run pass-through to retail). Granger causality tests confirm unidirectional relationships between farm prices and retail prices, reflecting market power in concentrated segments (HHI value of 2650). These findings underscore how market concentration distorts value chain equity. Policy recommendations include antitrust enforcement, transparency initiatives, and support for producer cooperatives to mitigate asymmetric power dynamics. Policies should also prioritize antitrust measures and cooperatives.